Prepurchase Information Acquisition and Credible Advertising - Gardete, Pedro M.; Guo, Liang (Management Science, 2021)
Consumers can decide whether to acquire more information about their valuations prior to purchase. In this paper, we examine pricing and advertising strategies when consumers can engage in prepurchase information acquisition. We show that consumer information acquisition can increase valuation heterogeneity and undermine a firm’s ability to extract consumer surplus. As a result, interestingly, a higher product quality can exert a nonmonotonic impact on equilibrium information acquisition, hurt firm profitability, and lead to lower consumer surplus. We also demonstrate that prepurchase information acquisition can be an endogenous mechanism to enable credible advertising in a cheap-talk setting. We show that quality claims in advertisements can be informative even when the firm can freely misrepresent its advertising message. Informative advertising can arise because a higher perceived quality can not only increase consumers’ expected value, but it also induces more information acquisition and thus hurts the firm’s ability to extract consumer surplus. This novel explanation for the credibility of cheap-talk advertising is distinguished from those identified in the literature (e.g., matching between firm types and heterogenous consumers, restrictive communication on multidimensional attributes). Moreover, we show that a higher quality can soften competition by inducing more information acquisition, thus benefiting the rival firm’s profitability. This paper was accepted by Matthew Shum, marketing.